2012
DOI: 10.1111/epi.12027
|View full text |Cite
|
Sign up to set email alerts
|

Current position of phenobarbital in epilepsy and its future

Abstract: SUMMARYThis article reviews the current position of phenobarbital using articles published since 2000 and speculates on its likely future contribution to epilepsy care. Over the last decade there have been no major double-blind randomized placebo-controlled or comparative trials with phenobarbital. Previous studies have suggested that phenobarbital is as effective in monotherapy as phenytoin and carbamazepine. Several observational studies undertaken in developing countries over the last decade have confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 57 publications
1
74
0
1
Order By: Relevance
“…Phenobarbital has an extremely low potential for misuse. 41 Its use in developed countries has been limited by a comparative trial that showed that phenobarbital and primidone (which is metabolized to phenobarbital) were less well tolerated than phenytoin or carbamazepine. 42 This finding is less relevant for resource poor countries when the only choice is between phenobarbital or no treatment at all.…”
Section: Box 1 | Disease Burden and Treatment Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenobarbital has an extremely low potential for misuse. 41 Its use in developed countries has been limited by a comparative trial that showed that phenobarbital and primidone (which is metabolized to phenobarbital) were less well tolerated than phenytoin or carbamazepine. 42 This finding is less relevant for resource poor countries when the only choice is between phenobarbital or no treatment at all.…”
Section: Box 1 | Disease Burden and Treatment Gapmentioning
confidence: 99%
“…The side effects of phenobarbital-mainly sedation, possible mild cognitive impairment, and depression-can be minimized by using the lowest possible effective dose. 41 Thus, phenobarbital is the current drug of choice for large scale, community based programs, particularly in rural and remote areas of developing countries. 41 Despite the availability of phenobarbital for more than 90 years and its modest cost, the treatment gap for epilepsy still exceeds 90% in many developing countries.…”
Section: Box 1 | Disease Burden and Treatment Gapmentioning
confidence: 99%
“…Compare to other AEDs greater like hood for PHB to be withdrawn compared with other AEDs possibly due to higher doses and concerns about its toxicity. 3 It is as effective in monotherapy to control seizures as phenytoin and carbamazepine. 4 So therefore need of the drugs that delay in development tolerance, improve cognitive function and reduce epilepsy induced oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used as an antiepileptic drug for it is complete and very effective drug and has advantages such as low cost, broad spectrum of action and ease of use (Dalmora et al, 2010). It is a centenarian drug and is still the best costbenefit pharmacological treatment for epilepsy, especially in developing countries (Brodie, Kwan, 2012).…”
Section: Introductionmentioning
confidence: 99%